Development and Advancement of Contemporary Islamic Judiciary/Islamic Law in Indonesia - Miftahul Jannah; Supardin S; Muh Rusti T (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The existence of religious courts demonstrates the state's recognition of Islamic law within the national legal system. Modern societal changes demand that Islamic law and religious courts effectively address contemporary issues through the development of Islamic law, which is influenced by globalization, technological advancements, and the demands of national legal reform. This study was conducted to examine the development and evolution of contemporary Islamic law/courts in Indonesia, along with their challenges and prospects. The method employed in this study is a literature review (library research), with data analysis conducted using a descriptive approach. The results of the research explain that the development and evolution of contemporary Islamic law/courts in Indonesia exist to confront and answer increasingly complex contemporary legal challenges. Among these developments in Islamic law are the codification of Islamic law, the growth of the Sharia economy, the digitalization of courts, and family law reform. Meanwhile, the development of the courts includes strengthening regulations, increasing the competence of religious courts, modernizing the judicial system, and integrating Islamic law with national law. In exercising its functions, the religious judiciary faces various challenges arising from the changing times and social shifts in society, leading to the emergence of several driving factors for the prospects of religious courts, fueled by the public's growing need for dispute resolution based on Islamic Sharia principles.